A case of severe dermatitis in a patient with Polycythemia Vera during cytoreductive therapy - Accurso V; Santoro M; Caputo V; Fiorella S; Casimiro P; Sardo M; Marino C; Sucato G; Siragusa S (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2019)
Polycythemia Vera (PV) is a Philadelphia-negative chronic myeloproliferative neoplasm (MPN) mainly characterized by erythrocytosis. In this report we describe a case of severe cutaneous toxicity in patients with PV treated with hydroxyurea. A 72-year-old woman diagnosed with PV with V617F mutation of JAK2 performed more than 10 years before and treated with hydroxyurea plus phlebotomies and low-dose ASA for about 7 years addressed our center for the appearance of serious dermatitis at the face symptomatic for severe itch. The patient underwent a dermatology visit with diagnosis of desquamative dermatitis due to iatrogenic cause related to the use of hydroxyurea. HU was stopped for a month with no improvement after a month of wash-out. Ruxolitinib was prescribed at a dose of 20 mg per day, in order to control hypercytosis and considering the severe intolerance to hydroxyurea. Ruxolitinib allowed not only to reduce the haematocrit, reaching the target value of 45%, and control thrombocytosis, but also to switch off the severe itch and to completely resolve skin toxicity.